International League Against Epilepsy classification and definition of epilepsy syndromes with onset in childhood: Position paper by the ILAE Task Force on Nosology and Definitions. Issue 6 (3rd May 2022) - Specchio, Nicola; Wirrell, Elaine C.; Scheffer, Ingrid E.; Nabbout, Rima; Riney, Kate; Samia, Pauline; Guerreiro, Marilisa; Gwer, Sam; Zuberi, Sameer M.; Wilmshurst, Jo M.; Yozawitz, Elissa; Pressler, Ronit; et al.
Abstract: The 2017 International League Against Epilepsy classification has defined a three‐tier system with epilepsy syndrome identification at the third level. Although a syndrome cannot be determined in all children with epilepsy, identification of a specific syndrome provides guidance on management and prognosis. In this paper, we describe the childhood onset epilepsy syndromes, most of which have both mandatory seizure type(s) and interictal electroencephalographic (EEG) features. Based on the 2017 Classification of Seizures and Epilepsies, some syndrome names have been updated using terms directly describing the seizure semiology. Epilepsy syndromes beginning in childhood have been divided into three categories: (1) self‐limited focal epilepsies, comprising four syndromes: self‐limited epilepsy with centrotemporal spikes, self‐limited epilepsy with autonomic seizures, childhood occipital visual epilepsy, and photosensitive occipital lobe epilepsy; (2) generalized epilepsies, comprising three syndromes: childhood absence epilepsy, epilepsy with myoclonic absence, and epilepsy with eyelid myoclonia; and (3) developmental and/or epileptic encephalopathies, comprising five syndromes: epilepsy with myoclonic–atonic seizures, Lennox–Gastaut syndrome, developmental and/or epileptic encephalopathy with spike‐and‐wave activation in sleep, hemiconvulsion–hemiplegia–epilepsy syndrome, and febrile infection‐related epilepsy syndrome. We define each, highlighting the mandatory seizure(s), EEG features, phenotypic variations, and findings from key investigations.